Who's there? - Tolan, Stephanie S. (Morrow Junior Books, 1994)
When fourteen-year-old Drew and her mute younger brother come to live with their father's estranged relatives after their parents' sudden death, they learn that the house is haunted by ghosts and discover a deadly family secret.